The facilitation of constructional meaning in the processing of Mandarin innovative Bei construction - Liao, Qiaoyun; Weng, Xin; Dong, Chao; Zhang, Yuxin (Frontiers in Psychology, 2023)
The processing of Mandarin innovative Bei construction in the form of “Bei + X” is different from that of the traditional Bei construction in that the former activates the constructional meaning which is intrinsically negative. This study thus investigates whether the processing of Mandarin innovative Bei construction is facilitated by the access of such emergent negative associations in a self-paced reading experiment with a priming paradigm. In this study, participants firstly read lexical primes in three conditions including construction-related phrases (i.e. phrases expressing the negative constructional meaning of the innovative Bei construction), component-related phrases (i.e. phrases expressing the partial literal meaning of the innovative Bei construction), and unrelated phrases (i.e. phrases expressing unrelated meaning to the innovative Bei construction). They then read sentences where the innovative Bei construction was fitted into and finally answered questions. Results showed that the lexical primes conveying the constructional meaning of the innovative Bei construction significantly shortened participants’ reading time duration as compared with another two priming conditions. To conclude, the processing of Mandarin innovative Bei construction is facilitated by the priming of its constructional meaning, which provides some psychological evidence for the construction-based processing of Mandarin innovative Bei construction.